Evaluation Analysis Reformulation Nusantara Moderate Ulama - Sani, Adul; Kumari, Fatrawati; Ainah, Noor (ProBisnis : Jurnal Manajemen, 2023)
Ulama Special Program (PKU) or Ulama Special Program with the same abbreviation, is a product of the initial Study Program (Prodi) of PKU Tafsir Hadith (TAHA) IAIN Antasari, before becoming UIN since 2005 became a superior program at IAIN, so many typical enthusiasts come from various parts of the island outside Kalimantan. The core of the program is to produce intellectual scholars who are able to combine religious knowledge (Islam and other sciences). Then it developed into PKU AFI (Akidah and Islamic Philosophy) Program with TAHA. Planning and management application and implementation in the field of implementation from student input, implementation and results are not all in accordance with planning and implementative management. Based on the problem of weak methodology of mastering the primacy of memorizing the Koran, mastering the basic science of keushuluddin and the main science of the study program such as the science of Akidah-Tasawuf-Akhlak and the science of logical sources (philosophy), plus there are still weaknesses in mastering the yellow book, English, and others, this study aims to analyze the evaluative recruitment of students, the process of non-regulated and special lectures, special religious guidance, special extra-curriculars, special financial assistance (scholarships) and additional programs in an 'exceptional' manner, so as to be able to produce prospective scholars with the formality of Higher Education. The research method is qualitative by analyzing the application of the program in the field in evaluative studies using observation, in-depth interviews and documentary methods. The results of the input, process and out-put targets, namely, although there are additional mastery such as Islamic boarding schools, yellow books and Arabic in scientific work from the results of the final thesis and coursework. Measured by academic achievement based on IP above 3.30 -3.75 plus. Another finding is the need to improve the jargon, the label of scientific content and the orientation of good morals, the ability to master local content Islamic science, as well as proposing a reformulation program (a more ideal improvement), with a new mission of producing or producing Nusantara-moderate scholars. Ulama-moderate-nusantara prioritizes ihsan - righteous deeds and community practices by and for the people. The soul of Islamist-modern nationalism, upholding the practices of the inheritors of the Apostles and Anbiya, but being a pioneer of the uniqueness of the archipelago